Outcomes of transoral endoscopic thyroidectomy vestibular approach versus endoscopic thyroidectomy via areola approach in the treatment of thyroid carcinoma: a meta-analysis - Wu, Jianyu; Xiao, Zhi; Liang, Weiming; Wang, Xiaojian; Liang, Xinyi; Yin, Shan; Yang, Yali; Quan, Jieru; Li, Zongyong; Hu, Chunge; Wei, Ping (Frontiers in Oncology, 2025)
IntroductionThis meta-analysis was designed to compare the outcomes of transoral endoscopic thyroidectomy vestibular approach (TOETVA) versus endoscopic thyroidectomy via the areola approach (ETAA) for thyroid carcinoma.Materials and methodsFive databases (PubMed, Embase, Web of Science, Cochrane Library, and Scopus) were systematically searched for studies comparing endoscopic thyroidectomy via TOETVA versus ETAA in patients with thyroid carcinoma. The search was conducted from the databases’ establishment to May 31, 2025. Operative time, intraoperative blood loss, number of central lymph node dissections, postoperative drainage volume, length of hospital stay, postoperative infection, hypoparathyroidism, perioperative recurrent laryngeal nerve injury, complication, hypocalcemia, subcutaneous ecchymosis, cough, trachyphonia, postoperative parathyroid hormone (PTH), postoperative blood calcium, pain score of Visual Analogue Scale (VAS), swallowing discomfort, hematoma, central lymph node dissection time, and satisfaction with cosmetic effects were subjected to meta-analyses.ResultsA total of 15 studies were included in the meta-analysis. The meta-analysis included a group of 1,961 patients diagnosed with thyroid carcinoma. Within this cohort, 777 patients underwent endoscopic thyroidectomy via TOETVA, while 1,184 patients underwent endoscopic thyroidectomy via ETAA. Compared with ETAA, TOETVA yielded lower intraoperative bleeding volume [weighted mean difference (WMD = −1 mL, 95% confidence interval (CI): −3 to 0, p = 0.03], higher number of central lymph node dissections (WMD = 1.4, 95% CI: 0.3 to 2.3, p = 0.02), and higher satisfaction with cosmetic effects of the patients (WMD = 0.93, 95% CI: 0.42 to 1.43, p = 0.0004), but longer operative time (WMD = 17 min, 95% CI: 8 to 26, p = 0.0002). There was no statistically significant difference between the two groups regarding postoperative drainage volume (WMD = −6 mL, 95% CI: −17 to 5, p = 0.31), postoperative infection [odds ratio (OR) = 1.43, 95% CI: 0.47 to 4.43, p = 0.53], perioperative recurrent laryngeal nerve injury (OR = 0.62, 95% CI: 0.30 to 1.28, p = 0.20), hypocalcemia (OR = 0.88, 95% CI: 0.40 to 1.91, p = 0.74), swallowing discomfort (OR = 0.83, 95% CI: 0.24 to 2.95, p = 0.78), hypoparathyroidism (OR = 0.47, 95% CI: 0.18 to 1.18, p = 0.11), and hospitalization time (WMD = 0.03 days, 95% CI: −0.13 to 0.19, p = 0.71).ConclusionsThe findings indicated that both TOETVA and ETAA demonstrated safe and reliable clinical efficacy. TOETVA offers additional benefits concerning satisfaction with cosmetic effects and central lymph node dissection. TOETVA is an optimal option for patients seeking scarless surgical procedures.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251021663.